Pandemic GII.4 Sydney and Epidemic GII.17 Kawasaki308 Noroviruses Display Distinct Specificities for Histo-Blood Group Antigens Leading to Different Transmission Vector Dynamics in Pacific Oysters - Morozov, Vasily; Hanisch, Franz-Georg; Wegner, K. Mathias; Schroten, Horst (Frontiers in Microbiology, 2018)
Noroviruses are the major cause of foodborne outbreaks of acute gastroenteritis, which are quiet often linked to raw oyster consumption. Previous studies have suggested histo-blood group antigens (HBGA)-like structures in the oyster tissues as ligands for norovirus binding and persistence. To better understand how oysters can function as vectors for common human noroviruses we have first tested the ability of the GI.1 West Chester, the pandemic GII.4 Sydney, and the epidemic GII.17 Kawasaki308 strains to interact with oyster tissues, and secondly explored how the HBGA preferences of these strains can affect their persistence in oyster tissues. We have found limited HBGA expression in oyster tissues. Only A and H type 1 HBGAs were present in digestive tissues and palps of the Pacific oyster Crassostrea gigas, while gills and mantle lack any HBGA structures. Virus-Like particles (VLPs) of the GI.1 West Chester norovirus reacted with the digestive tissues and palps. Despite of the lack of HBGA expression in mantle, dominant GII.4 Sydney strain readily bound to all the oyster tissues, including digestive tissues, gills, palps, and mantle. In contrast, no binding of the epidemic GII.17 Kawasaki308 VLPs to any oyster tissues was observed. In synthetic HBGA and saliva-binding assays, GI.1 reacted with A type, H type, and Lewis b HBGAs. GII.4 Sydney VLPs showed a broad binding pattern and interacted with various HBGA types, including H type 1 structures. Compared to GI.1 and GII.4 VLPs, the GII.17 Kawasaki308 VLPs only weakly associated with HBGAs carbohydrates and mainly exhibited low affinity binding to long-chain saccharides containing A type, B type, H type, Leb blood group epitopes. Our findings therefore indicate that GI.1 and GII.4 noroviruses are likely to be concentrated in the oysters via HBGA-like glycans potentially leading to increased long term transmission, while for the GII.17 Kawasaki308 strain oysters can only function as short term transmission vectors in periods of high environmental virus concentrations.